PoC GTFO. - Laphroaig, Manul (No Starch Press, 2018)
PoC or GTFO, Volume 2 follows-up the wildly popular first volume with issues 9-13 of the eponymous hacker zine. Contributions range from humorous poems to deeply technical essays.The International Journal of Proof-of-Concept or Get The Fuck Out is a celebrated magazine of reverse engineering, retro-computing, and systems internals. This second collected volume holds all of the articles from releases nine to thirteen.Learn how to patch the firmware of a handheld amateur radio, then emulate that radio's proprietary audio code under Linux. How to slow the Windows kernel when exploiting a race condition and how to make a PDF file that is also an Android app, an audio file, or a Gameboy speedrun. How to hack a Wacom pen table with voltage glitching, then hack it again by pure software to read RDID tags from its surface. How to disassemble every last byte of an Atari game and how to bypass every classic form of copy protection on Apple ][.But above all else, beyond the nifty tricks and silly songs, this book exists to remind you what a clever engineer can build from a box of parts with a bit of free time. Not to show you what others have done, but to show you how they did it so that you can do the same.--Provided by publisher.